2021
DOI: 10.1002/ece3.7729
|View full text |Cite
|
Sign up to set email alerts
|

Damselfly eggs alter their development rate in the presence of an invasive alien cue but not a native predator cue

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 57 publications
2
18
2
Order By: Relevance
“…For example, exposure to the native dragonfly cue increased the growth rate independently of the latitude of origin [ 31 ]. Exposure to the invasive alien spiny-cheek crayfish cue reduced the egg development time compared with exposure to cues from other native and nonnative predator species [ 39 ]. Hence, the use of the spiny-cheek crayfish may lead to different responses in coping with the predator cue, which might depend on damselfly co-occurrence with the more or less phylogenetically related predator species [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, exposure to the native dragonfly cue increased the growth rate independently of the latitude of origin [ 31 ]. Exposure to the invasive alien spiny-cheek crayfish cue reduced the egg development time compared with exposure to cues from other native and nonnative predator species [ 39 ]. Hence, the use of the spiny-cheek crayfish may lead to different responses in coping with the predator cue, which might depend on damselfly co-occurrence with the more or less phylogenetically related predator species [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the use of the spiny-cheek crayfish may lead to different responses in coping with the predator cue, which might depend on damselfly co-occurrence with the more or less phylogenetically related predator species [ 40 ]. Thus, shorter development time in central-latitude individuals may be part of an avoidance strategy to reduce the time of exposure prior to emergence to their nonnative aquatic predator, but at the cost of having a lower mass [ 39 , 41 ]. Regarding larval size, some studies on other damselfly species found positive correlations between body size and swimming speed as a way to escape predators [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antagonistic interactions can change larval behavior to avoid predation 32 . Previous studies showed that life history traits in damselflies are altered by non-consumptive predator stress 33 , 53 , 64 , 82 84 and temperature 53 , 85 , 86 . But in these studies, the focus was on predator stress on the egg stage or on individually reared larvae, thereby precluding cannibalism.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of stressors may change a strategy in potential prey to escape predator exposure (Warkentin, 2011). Here, an accelerated larval growth in the presence of a predator cue under heat wave may be part of an escape strategy to reduce the time of exposure to predators, as previously shown in odonate species (Antoł & Sniegula, 2021;Stoks et al, 2012) and other taxa (Chivers et al, 2001).…”
Section: Effects On Individual Traitsmentioning
confidence: 89%